Conditions for success in teaching and learning English in the Philippines a system approach - Maminta, Rosario E.
In the Philippines, success in teaching English will most likely be achieved if the goals of instruction reflect the needs of Filipino learners as members of Philippine society. If the elarner sees that these goals are relevant, he becomes a willing learner. But this, by itself does not guarantee condition for success. Since the elarning-teaching situation is a cooperative enterprise, another necessary condition is a skillfull teacher. To summarise, Stevens atates that achievement is highest when skilled teachers are encouraged by society and their profession to cherish willing learners.
Keywords: English language -- Study and teaching -- Philippines; Bilingualism -- Philippines; Language policy -- Philippines